Knowledge, Attitude and Practice of Community Pharmacy Staffs Toward Pharmacovigilance and Reporting of Adverse Drug Reactions in Sulaimani City: A Cross Sectional Study - Khanda Taifwr Hamasalih; Bushra Hassan Marouf (Iraqi Journal of Pharmaceutical Sciences)
Pharmacovigilance (PhV) is the science that is essential for detecting, preventing and reducing the adverse drug reactions (ADRs). Its main goal is to ensure the safety of post-marketing medications. This study is designed to determine the knowledge, attitude and practice of the pharmacy staffs (pharmacists and their assistants) toward PhV and ADRs reporting in the community pharmacies in Sulaimani City-Kurdistan Region-Iraq. The study designed as a cross-sectional face-to-face interview survey. A self-administered questionnaire was used in this study, the interviews were conducted from June to October 2022, a total of 141 pharmacists and their assistants in 60 community pharmacies were recruited for this study. The total number of responses was 131(93%). Basically, the finding of the current study revealed that more than half of the community pharmacy staffs were familiar to the term and aim of PhV. However, their knowledge on PhV and ADRs reporting was poor and inadequate. Generally, participants showed a positive attitude towards the aspects of PhV and ADRs reporting. 63.4% believed that the PhV is an important and essential element for safety of post-marketing medications. Despite this positive attitude, only 7.6% of the participants had previously reported an ADRs during their practice. 46.56% of the community pharmacists and their assistants stated that they were not-reporting ADRs because they were unmotivated. In conclusion, the majority of the pharmacy staffs were knowledgeable about the concepts of PhV and had agreed that reporting of ADR is necessary, but the reporting rate was very poor and inadequate. Integration of PhV in an interactive training course is needed to increase the awareness of ADRs reporting by healthcare professionals. Pharmacovigilance should also be taught in detail as a part of pharmacy undergraduate curriculum. Conducting workshops or courses to understand the reporting process is crucial to increase ADRs reporting.